Peranan Relationship Marketing pada Keputusan Nasabah dalam Menggunakan Tabungan IB Haji di PT Bank KB Bukopin Syariah Cabang Bukittinggi - Mulyani, Devi Sri; Martilova, Novera (Lembaga Yasin AlSys, 2024)
This research is motivated by fluctuations in the percentage increase in the number of savings customers. IB Hajj at PT Bank Kb Bukopin Syariah Bukittinggi Branch, because relationship marketing is an approach taken by Relationship Officers to prospective customers. Current research aims to find out what or how the Role of Relationship Marketing on Customer Decisions in Using IB Hajj Savings at PT Bank Kb Bukopin Syariah Bukittinggi Branch. The research conducted by the author is using a method with a qualitative approach, where the data sources taken by the author are primary data and secondary data. As for the data collection techniques, namely observation techniques, interviews and field documentation techniques. And the data analysis technique carried out by the author is obtained through data analysis, namely reduction, display, conclusions and data verification. Through the results of research and analysis that has been done by the author, it can be concluded that relationship marketing is very instrumental in making customer decisions in using IB Hajj savings at PT Bank KB Bukopin Syariah Bukittinggi Branch. This can be seen from the increasing number of customers, increasing the trust of prospective customers in making decisions to use IB Hajj savings, establishing a good relationship between prospective customers and the bank and can also establish a good relationship between prospective customers and PT Bank KB Bukopin.